Preliminary Study on Youth Lifestyle with Regards to Energy Saving - Salleh, Nur Shakirah Md (International Journal of Engineering and Technology, 2018)
The advancement of information and communication technology (ICT) leads the increasing number of digital devices. The paper focuses on a preliminary study in discovering the youth lifestyle including electricity usage and preferred electricity appliances towards energy saving. This research carried out one of the data gathering techniques; survey, to find the level of the youth lifestyle towards energy saving among youth in a higher level-learning institute. This paper shares the processes and algorithm in finding the result of this type of study. The results derived from the algorithm show that 67.15% of the respondents are implementing energy saving in their lifestyle. This lifestyle partially influences their preferences in choosing electrical appliances with 78.74% of the respondents are looking forward to energy saving products that comes with a known brand and affordable price.